Distributed Proxy Re- Encryption Protocol for Secure Multiparty Computation with Fully Homomorphic Encryption - Demir, Busranur Bulbul; Altilar, Deniz Turgay (International Black Sea Conference on Communications and Networking, 2024)
Secure computation is required to protect data security and privacy. Homomorphic encryption is known as a safe way for secure computation. However, it comes with limitations such that the ciphertexts to be evaluated must be encrypted with the same key. In the multiparty system, homomorphic evaluation becomes more complex apart from the existing complexity of the homomorphic encryption because of the limitation. In this article, the multi party homomorphic evaluations that are available in the literature are investigated and a novel design is proposed. Distributed proxy re-encryption algorithm that is available for untrusted or semi-trusted system is presented besides distibuted decryption protocol. The pro-posed design is implemented with k-nearest neighbors (KNN) classification algorithm and the results are evaluated in terms of security, privacy and efficiency. The suggested protocol increases operational efficiency while the data security and privacy are provided.